TINDAK TUTUR KEARIFAN LOKAL YOGYAKARTA PADA FILM-FILM PENDEK DI KANAL YOUTUBE PANIRADYA KAISTIMEWAN - Fatonah, Devi Umi; Nurhayati, Endang (Widyaparwa, 2024)
This research aims to reveal the types, characteristics and functions of speech acts that show Yogyakarta local wisdom in short films on the Paniradya Kaistimewan YouTube channel. This research uses a sociopragmatic approach with descriptive qualitative research methods. The data in this research is speech in the form of words, phrases, clauses or sentences that show the local wisdom of Ngayogyakarta in short films on the Paniradya Kaistimewan YouTube channel. How to collect data by listening, making transcriptions and writing speeches. The research tool used is the researcher himself, assisted by data cards. How to validate data using semantic validity, theoretical triangulation, and stability reliability. The results of the research show: 1) direct literal with the characteristics of using the lingual unit "nuwun sewu" and the request directive function, 2) direct literal with the characteristics of using the lingual unit "nyuwun pangapunten" and the expressive function "nyuwun pangapunten", 3) direct literal with the characteristics of using the lingual unit "matur nuwun" and the expressive function of saying thank you, 4) direct literal with the characteristics of using the word "mangga" and the directive function of giving orders, 5) direct literal with the characteristics of using the word "injih ” and the representative function of providing an explanation, and 6) directly not literal with the characteristics of using the word “mango” and the directive function of request.Penelitian ini bertujuan mengungkap jenis, ciri-ciri, dan fungsi tindak tutur yang menunjukkan kearifan lokal Yogyakarta pada film pendek di kanal Youtube Paniradya Kaistimewan. Penelitian ini menggunakan pendekatan sosiopragmatik dengan metode penelitian kualitatif yang bersifat deskriptif. Data pada penelitian ini tuturan yang berwujud kata, frasa, klausa, atau kalimat yang menunjukkan kearifan lokal Ngayogyakarta pada film-film pendek di kanal Youtube Paniradya Kaistimewan. Cara mengumpulkan data dengan menyimak, membuat transkripsi, dan menulis tuturan Alat penelitian yang digunakan yaitu peneliti sendiri dibantu kartu data. Cara mengesahkan data menggunakan validitas semantis, triangulasi teori, dan reliabilitas stabilitas. Hasil penelitian menunjukkan: 1) langsung literal dengan ciri-ciri menggunakan satuan lingual “nuwun sewu” dan fungsi direktif permintaan, 2) langsung literal dengan ciri-ciri menggunakan satuan lingual “nyuwun pangapunten” dan fungsi ekspresif “nyuwun pangapunten”, 3) langsung literal dengan ciri-ciri menggunakan satuan lingual “matur nuwun” dan fungsi ekspresif mengucapkan terima kasih, 4) langsung literal dengan ciri-ciri menggunakan kata “mangga” dan fungsi direktif memberi perintah, 5) langsung literal dengan ciri-ciri menggunakan kata “injih” dan fungsi representatif memberi penjelasan, serta 6) langsung tidak literal dengan ciri-ciri menggunakan kata “mangga” dan fungsi direktif permohonan.